Leveraging Big Data to Improve Biometric Algorithms for Real-Time Authentication in Digital Commerce (International Journal of Engineering and Computer Science, 2024)
The rapid growth of digital commerce has intensified the need for secure, efficient, and user-friendly authentication methods. Traditional authentication techniques, such as passwords and PINs, are increasingly vulnerable to cyber threats, prompting the exploration of more advanced solutions. This research investigates the integration of big data with biometric authentication systems to improve real-time identity verification processes in digital commerce. By leveraging big data analytics, biometric algorithms can achieve higher accuracy, scalability, and adaptability, providing more robust security and a seamless user experience. The study highlights how big data enables the enhancement of biometric algorithms through continuous learning, real-time data processing, and the combination of multiple biometric modalities (e.g., fingerprint, facial recognition, and voice). It explores the potential of machine learning and artificial intelligence to fine-tune biometric systems, addressing challenges such as false acceptance/rejection rates and improving system responsiveness. Furthermore, the research identifies key challenges, including data privacy concerns, algorithmic bias, ethical issues, and technical constraints related to processing large volumes of biometric data in real-time. The research also examines the future trajectory of biometric authentication in digital commerce, emphasizing advancements in multi-modal biometrics, quantum encryption, and continuous authentication. As these technologies evolve, they promise to make biometric systems more secure, efficient, and accessible. Despite the challenges, the integration of big data in biometric authentication holds great potential to redefine the landscape of digital commerce by offering a safer, more user-friendly experience for consumers worldwide.